Factor that influence loan repayment default among national higher education fund corporation (NHEFC) borrower: case study among UiTM Segamat graduates intake September 2013 / Nur Athikah Mohamad Dzahir - Nur Athikah, Mohamad Dzahir (Faculty of Business Management, University Teknology MARA, 2018)
Government has introduced National Higher Education Fund Corporation (NHEFC) established in 1997 and had given study loans to 2.6 million students. Furthermore, almost half a million National Higher Education Fund Corporation (NHEFC) borrowers have not paid a single cent of RM 2.79 billion and caused NHEFC lack of money to provide loan to new student. Malaysia graduate failed to secure opportunities for job because of attitude and proved one in four fresh graduates in Malaysia remains unemployed within six month after graduates. The study conducted purpose to investigate whether age, attitude, knowledge, and intention to pay loan will affect the loan repayment default among UiTM Segamat graduates. The research design for this study employ quantitative method of systematic sampling and questionnaire that developed by referring detailed relevant literature. The dependent variable is loan repayment default and independent variable are age, attitude, knowledge and intention to pay. The sample used in this study is UiTM Segamat intake September 2013 graduates by distribute 150 questionnaires. Then, data collected will be analyzed using SPSS to generate Descriptive Analysis, Reliability Analysis, Factor Analysis, Correlation Analysis and Regression Analysis to test effect of (age, attitude, knowledge and intention to pay) towards loan repayment default. The finding of this study will be useful insight of NHEFC, UiTM and NHEFC borrower. Finding from research conducted indicate there is high correlation between age, attitude, knowledge and intention toward loan repayment default. However only age, knowledge and intention are significant at (p = 0.001) (p = 0.000) and (p = 0.054) respectively meanwhile, attitude is not significant.